Activation of Nucleases, PCD, and Mobilization of Reserves in the Araucaria angustifolia Megagametophyte During Germination - Moyano, Laura; Correa, María D.; Favre, Leonardo C.; Rodríguez, Florencia S.; Maldonado, Sara; López-Fernández, María P. (Frontiers in Plant Science, 2018)
Nuclease activation, DNA fragmentation and reserve mobilization in the megagametophyte of Araucaria angustifolia, in the mature seeds, consists of cells with thin walls, one or more nuclei, a central vacuole storing proteins, and a cytoplasm rich in amyloplasts, mitochondria and lipid bodies. In this study, we describe the process of mobilization of reserves and analyzed the dismantling of the tissue during germination, using a range of well-established markers of programmed cell death (PCD), including: morphological changes in nuclei and amyloplasts, DNA degradation, and changes in nuclease profiles. TUNEL reaction and DNA electrophoresis demonstrated that DNA fragmentation in nuclei occurs at early stages, which correlates with induction of specific nucleases. Our study provides the first results on the dismantling of a storage tissue that stores starch as the main reserve substance. We consider that this study describes a different pathway of PCD and reveals new insights into the role of nucleases and the expression patterns of putative nuclease genes during germination.